Afrodescendant memory in Brazilian museums: the case of the Mariano Procópio Museum - Christo, Maraliz de Castro Vieira (PORTO ARTE: Revista de Artes Visuais, 2019)
Abstract The Mariano Procópio Museum originated from a private collection, formed between the 19th and 20th centuries, by Alfredo Ferreira Lage, and donated by him to the city of Juiz de Fora. By identifying representations of African descendence in the collection, we question its origin. They can be grouped into three categories: those acquired by the institution, reinforcing a conservative discourse; those donated by the artists themselves spreading their works; and, most of them, those who received the City’s acquisitive prize, when exhibited at the Salon of the Society of Fine Arts Antonio Parreiras, from 1950 to 1980, and were allocated in the museum, breaking old canons. Resumo O Museu Mariano Procópio originou-se de uma coleção particular, formada entre os séculos XIX e XX, por Alfredo Ferreira Lage, e doada por este ao município de Juiz de Fora. Ao identificarmos representações de afrodescendentes no acervo, nos interrogamos sobre sua procedência. Pode-se agrupá-las em três categorias: as adquiridas pela instituição, reforçando um discurso conservador; aquelas doadas pelos próprios artistas difundindo seus trabalhos; e, a maioria, as que receberam o prêmio aquisitivo da prefeitura, quando expostas no Salão da Sociedade de Belas Artes Antônio Parreiras, entre os anos de 1950 a 1980, e foram alocadas no museu, rompendo antigos cânones.